PERANCANGAN DAN IMPLEMENTASI SISTEM SMARTFARMING MENGGUNAKAN ARDUINO UNO DAN MODUL ESP8266 - Bijanto Bijanto; Sigit Prakosa Adi Nugroho; Yayang Fredyatama; Dini Fahrani; Ellen Proborini (Jurnal Disprotek, 2023)
The agricultural sector is a promising sector in the future, but in Indonesia the agricultural sector has not developed properly due to many factors such as individual land ownership which tends to be narrow, young people who do not want to continue their parents' business in farming, then 60% of farmers in Indonesia still relies on traditional farming systems, regardless of water needs, seasons, climate, sales prices, types of plants and others. Traditional farming systems also require high costs, so the income is less than optimal. According to BPS, in the second quarter of 2022 the highest economic sector was found in the business fields of agriculture, forestry and fisheries at 13.15%. This potential should be developed in the industrial era 4.0, as an example of technology that can be applied in the agricultural sector, namely the Internet of Think, a system is needed to control water demand, temperature and light intensity needed to help plant photosynthesis. The proposed system will use four sensors including a light sensor (LDR), a temperature sensor (dht-11), an ultrasonic sensor, and a soil moisture sensor. In this proposed system monitoring can also be carried out using the Blynk application which can be monitored via a smartphone. The system development process uses the Rnd method, because the Rnd method is suitable for making products that can be applied to support agriculture.